2011
DOI: 10.4304/jltr.2.6.1227-1237
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Lexical Inferencing Strategies and L2 Proficiency of Iranian EFL Learners

Abstract: Abstract-This paper tries to find out what knowledge sources Iranian EFL learners used while trying to infer the meaning of unknown words in the context. It is also intended to find out whether the students' level of L2 proficiency would affect the pattern of their use of the knowledge sources, and if there is a relationship between students' lexical inferencing strategy and their sex. To conduct the study, forty Iranian EFL learners, studying English at the private language institute, were selected to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This study also supports the significant relationship between lexical inference ability and reading comprehension. This finding is compatible with that resulted from the studies conducted by Sadeghi et al, (2018), Buslon, & Alieto (2018), Chegeni & Tabatabaei (2014), Awani (2013), Tavakoli and Hayati (2011), Nakagawa (2006), and Seng (2007. Their justification for this finding is the participants' scores in reading comprehension test which showed much variation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also supports the significant relationship between lexical inference ability and reading comprehension. This finding is compatible with that resulted from the studies conducted by Sadeghi et al, (2018), Buslon, & Alieto (2018), Chegeni & Tabatabaei (2014), Awani (2013), Tavakoli and Hayati (2011), Nakagawa (2006), and Seng (2007. Their justification for this finding is the participants' scores in reading comprehension test which showed much variation.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the vital role of the lexical inferencing strategies in helping LS and EFL learners in making acceptable guessing from texts and utilizing lexical inferencing strategies that help them understand materials written in English in their majors, many researches in recent years have investigated the topic of the effect of the lexical inferencing strategy instruction on EFL readers (Bengeleil & Paribakht, 2004;Nakagawa, 2006;Tavakoli & Hayati, 2011;Kaivanpanah & Moghaddam, 2012;Hu & Nassaji, 2014;Safa & Kokabi, 2017;Muikku-Werner, 2017, Buslon & Alieto, 2019. Such researches indicate the positive effect of the lexical inference strategies on reading comprehension and problems in inferring the meanings of vocabulary from context.…”
Section: Introductionmentioning
confidence: 99%
“…According to Comer (2012), this category could also be described as "un explained guessing" and is a differentiating characteristic of guessing vs inferencing. Whereas guessing is random and unexplained by the reader, inferencing is reasoned and explained (Tavakoli & Hayati, 2011).…”
Section: Code 9: Guessing (Gues)mentioning
confidence: 99%
“…It was also shown that successful students use more frequently reading strategies than unsuccessful ones. Similarly, Tavakoli and Hayati (2011), explored reading strategies use by Iranian EFL learners while inferring the meaning of unknown words from the context. They also examined whether learners' L2 proficiency level affects their use of reading strategies.…”
Section: Literature Review 21 Self-regulated Learningmentioning
confidence: 99%